If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -1(3x + 5) = 3x + -23 Reorder the terms: 9x + -1(5 + 3x) = 3x + -23 9x + (5 * -1 + 3x * -1) = 3x + -23 9x + (-5 + -3x) = 3x + -23 Reorder the terms: -5 + 9x + -3x = 3x + -23 Combine like terms: 9x + -3x = 6x -5 + 6x = 3x + -23 Reorder the terms: -5 + 6x = -23 + 3x Solving -5 + 6x = -23 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -5 + 6x + -3x = -23 + 3x + -3x Combine like terms: 6x + -3x = 3x -5 + 3x = -23 + 3x + -3x Combine like terms: 3x + -3x = 0 -5 + 3x = -23 + 0 -5 + 3x = -23 Add '5' to each side of the equation. -5 + 5 + 3x = -23 + 5 Combine like terms: -5 + 5 = 0 0 + 3x = -23 + 5 3x = -23 + 5 Combine like terms: -23 + 5 = -18 3x = -18 Divide each side by '3'. x = -6 Simplifying x = -6
| 18/3+2*6+7 | | 1/8(8t-5)=t+5/16 | | 10(2)+570=y | | 10(0)+570=y | | 4b-7=-14 | | 2x^2+3=4x+7 | | 2*5-6+21/3 | | 8y+0.04(y+2000)=1840 | | c=10h+20 | | 3+4*6-14/2 | | 4.5(1)+4=y | | 3a+4=5 | | 7log(4x+1)=11 | | 4.5(0)+4=y | | 2x-3=20/x | | 6(1)-2y=12 | | -.3(x-4)+x=.5(3-x) | | -1/2(0)-3=y | | 10x-1=-21 | | 1/2(0)-3=y | | -1/2(2)-3=y | | -3(4x+3)+5(6x+1)=43 | | 20/5+5+3x8 | | 20/5+5+5+3x8 | | (3/4x^2)+(8x)+20=0 | | 3/4x^2+8x+20 | | x=40+108 | | 5x+7=-10x-14 | | 576x^3-46x+8=0 | | 8x^2/3=2x+3 | | 40+110=x | | 7.19-{-3.2}= |